THE VALUE OF TEACHING-LEARNING RELIGIOUS EDUCATION TO STUDENTS IN THE 21ST CENTURY EDUCATIONAL SYSTEMS - Thomas, Fr. Baiju (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
The contemporary study on fostering the value of teaching-learning religious education (RE) to students in the 21st century educational systems. With the trend toward more emphasis on science disciplines and technical advancement, whether or not RE should be taught in public schools has recently been at the heart of much dispute. RE is challenging to instruct since there is no reliable method for integrating lessons into a child's classroom. Teachers should welcome new solutions to RE teaching and evaluations and encourage their students to take part in experiences that may cause them to reconsider or broaden their views of the world. RE teachers should reflect their students' values and beliefs and see them at work in their everyday interactions and in the classroom. Outcomes showed that various stakeholders prioritized learning different soft skills as part of a RE program. For the most part, respondents felt that tolerance and fairness should be highlighted more in RE classes. In the future, it was predicted that both religious literacy and digital literacy would receive increased focus. Success in RE was also posited to require the ability to think critically. Spiritual lessons were favored above more modern subjects like economics and technology. When we talk about "religious education," we are talking about introducing kids to Religion for its own sake, whether that is because they are being called to a particular faith or because it is something that deserves to be read with respect and attention. Many political systems keep a careful eye on religious education and spark passionate debate. Diverse religious interpretations and levels of education are two of the known aspects of the interaction between religious communities and public policies in post-industrial political groups. Moreover, most RE programs concentrate on memorizing rather than fostering creativity and critical thinking. Teachers in higher education are discussing and adopting instructional modifications similar to what should be taught in secondary school religious education classes to prepare students for success in the 21st century educational systems.